Cytologic characterization of atypical teratoid/rhabdoid tumor in cerebrospinal fluid. Issue 12 (4th August 2014) - Huang, Eric C.; Guzman, Miguel A.; De Girolami, Umberto; Cibas, Edmund S.
<x xml:space="preserve">Abstract</x> BACKGROUND Atypical teratoid/rhabdoid tumor (AT/RT) is a rare and highly aggressive intracranial malignancy with a predilection to spread along the cerebrospinal fluid (CSF) pathways. To the authors' knowledge, the cytopathologic characteristics of this tumor have not been extensively studied in CSF. Herein the authors report CSF cytomorphology from a series of patients with histologically documented AT/RT. METHODS A retrospective review of 40 malignant CSF specimens from 10 patients with histologically confirmed AT/RT was conducted. All the patients were female and ranged in age from 0.8 to 19.6 years at the time of the initial diagnosis (median age, 1.3 years). Cytospin preparations were reviewed. In the majority of cases, at least 2 slides were prepared with the Wright‐Giemsa and/or Papanicolaou stains. RESULTS The CSF samples were predominantly moderately to highly cellular (80%). The 3 most common features were eccentrically placed nuclei (72.5%), prominent nucleoli (70%), and large tumor cells (67.5%). Two principal malignant cell types were noted; the most striking and recognizable form was a large, usually rhabdoid cell with an eccentrically placed nucleus, prominent nucleolus, and abundant cytoplasm, which was observed in 47.5% of the cases. The second type had a small cell appearance and was noted in 57.5% of the cases. Both large rhabdoid and small malignant cells were reported in 25% of the cases. CONCLUSIONS A significant percentage of CSF AT/RT cases consist of only the small cell component, without the characteristic large rhabdoid cells. Familiarity with this pattern of spread is imperative in differentiating AT/RT from other small cell malignancies such as medulloblastoma, because the clinical behavior and therapeutic regimens differ. Cancer (Cancer Cytopathol) 2014;122:903–908. © 2014 American Cancer Society.